A type IV Autotaxin inhibitor ameliorates acute liver injury and nonalcoholic steatohepatitis. Issue 9 (14th July 2022) - Booijink, Richell; Salgado‐Polo, Fernando; Jamieson, Craig; Perrakis, Anastassis; Bansal, Ruchi
Abstract: The lysophosphatidic acid (LPA) signaling axis is an important but rather underexplored pathway in liver disease. LPA is predominantly produced by Autotaxin (ATX) that has gained significant attention with an impressive number of ATX inhibitors (type I‐IV) reported. Here, we evaluated the therapeutic potential of a (yet unexplored) type IV inhibitor, Cpd17, in liver injury. We first confirmed the involvement of the ATX‐LPA signaling axis in human and murine diseased livers. Then, we evaluated the effects of Cpd17, in comparison with the classic type I inhibitor PF8380, in vitro, where Cpd17 showed higher efficacy. Thereafter, we characterized the mechanism‐of‐action of both inhibitors and found that Cpd17 was more potent in inhibiting RhoA‐mediated cytoskeletal remodeling, and phosphorylation of MAPK/ERK and AKT/PKB. Finally, the therapeutic potential of Cpd17 was investigated in CCl4 ‐induced acute liver injury and diet‐induced nonalcoholic steatohepatitis, demonstrating an excellent potential of Cpd17 in reducing liver injury in both disease models in vivo . We conclude that ATX inhibition, by type IV inhibitor in particular, has an excellent potential for clinical application in liver diseases. Synopsis: The type IV ATX inhibitor Cpd17 hinders the ATX‐LPA signaling axis by abrogating RhoA‐mediated cytoskeletal remodeling and phosphorylation of MAPK and AKT. Cpd17 also ameliorated induced liver injury in mice, showing a potential for clinical application of type IV ATX inhibitors in liver disease. The involvement of the ATX‐LPA signaling axis in liver disease was confirmed by increased levels of ATX gene and protein expression in human patients and murine livers with induced injury. The type IV ATX inhibitor Cpd17 reduced disease‐relevant phenotypes in cell‐based assays performed in hepatocytes, macrophages, and hepatic stellate cells, more efficiently than the type I inhibitor PF8380. Inhibition of LPA G‐protein‐coupled receptor signaling, as monitored by the Gα(12/13)‐mediated RhoA activation and the Gα(i/o)‐mediated phosphorylation of MAPK/ERK and AKT/PKB, was more potent with Cpd17 than with PF8380. Administration of Cpd17 to mice with CCl4‐induced acute liver injury or diet‐induced nonalcoholic steatohepatitis, drastically improved liver histology and relevant plasma markers as alanine and aspartate aminotransferases, triglycerides, and cholesterol. Abstract : The type IV ATX inhibitor Cpd17 hinders the ATX‐LPA signaling axis by abrogating RhoA‐mediated cytoskeletal remodeling and phosphorylation of MAPK and AKT. Cpd17 also ameliorated induced liver injury in mice, showing a potential for clinical application of type IV ATX inhibitors in liver disease.